Eco-Friendly Pedagogy: Utilizing Recycled Materials in Stamping Activities to Foster Pre-Writing Skills in Toddlers - Ifah Nurrohmah; Aip Syarifudin; Irfan Fauzi Rahmat (Qualitative and Quantitative Research Center, 2026)
Pre-writing readiness in toddlers aged 2.5 to 3 years requires fine sensory-motor integration, yet conventional early childhood instruction heavily relies on abstract paper-and-pencil worksheets that frequently induce motor fatigue and disinterest. Grounded in Gibson's Affordance Theory and Eco-Friendly Pedagogy, this study evaluated the efficacy of a two-dimensional stamping intervention utilizing upcycled loose-part materials to foster graphic-motor readiness in early childhood classrooms. Employing a Practitioner-Led Action Research design embedded within a Design-Based Research framework across two cycles, the investigation involved a purposive sample of 14 toddlers aged 2.5 to 3 years at an early childhood learning center. Data were collected using a validated Graphic-Motor Readiness Rubric and analyzed using non-parametric statistics, with inter-rater reliability confirmed by Cohen's Kappa (k = 0.86). Quantitative findings demonstrated a statistically significant improvement in graphic-motor skills, with the overall median score progressing from 1.50 at baseline (IQR = 0.50) to 2.60 in Cycle II (IQR = 0.50), achieving a 65.1 percent target mastery rate. Wilcoxon Signed-Rank Testing confirmed significant cumulative performance gains (Z = -3.32, p = 0.001) accompanied by an exceptionally large effect size (r = 0.89). Qualitative observations revealed a dramatic surge in behavioral task persistence, expanding from an average of less than 4 minutes during worksheet tasks to 18 to 22 minutes per eco-stamping session. Upcycled materials functioned as active sensorimotor catalysts whose tactile affordances elicited adaptive digital grasp mechanics and dynamic force regulation. This study provides a cost-effective, sustainable pedagogical model for replacing abstract worksheets with tactile loose-part experiences in early childhood education.